Interview 4 - Abubakari, Yushawu
This file contains the interview notes with the Controller. The Controller (Pseudonymize) is 30years old and married with 1 kid. The Controller lives in an extended family house and still working on his own house. The controller has been in the scamming business for 5 years.. The controller started scamming after completing his first degree without any job. The interview was conducted in a restaurant near the Controller’s house